2005
DOI: 10.1063/1.2121347
|View full text |Cite
|
Sign up to set email alerts
|

On-axis parallel ion speeds near mechanical and magnetic apertures in a helicon plasma device

Abstract: Using laser-induced fluorescence, measurements of parallel ion velocities were made along the axis of a helicon-generated Ar plasma column whose radius was modified by spatially separated mechanical and magnetic apertures. Ion acceleration to supersonic speeds was observed 0.1–5cm downstream of both aperture types, simultaneously generating two steady-state double layers (DLs) when both apertures were in place. The DL downstream of the mechanical aperture plate had a larger potential drop, ΔϕDL=6–9kTe, compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 32 publications
0
31
0
Order By: Relevance
“…In a series of experiments on the Magnetized Nozzle eXperiment, multiple double layers were intentionally created by introducing grounded apertures upstream from a magnetic nozzle. 17 Axially resolved LIF measurements demonstrated that ions accelerated in the sheath formed by the aperture traveled nearly 30 cm to the magnetic nozzle where they were further accelerated by the double layer at the magnetic nozzle. Between the grounded aperture and the magnetic nozzle, a single accelerated ion population and the background ions created beyond the aperture were both observed with LIF.…”
Section: Lif Measurements Of Multiple Ion Beamsmentioning
confidence: 99%
“…In a series of experiments on the Magnetized Nozzle eXperiment, multiple double layers were intentionally created by introducing grounded apertures upstream from a magnetic nozzle. 17 Axially resolved LIF measurements demonstrated that ions accelerated in the sheath formed by the aperture traveled nearly 30 cm to the magnetic nozzle where they were further accelerated by the double layer at the magnetic nozzle. Between the grounded aperture and the magnetic nozzle, a single accelerated ion population and the background ions created beyond the aperture were both observed with LIF.…”
Section: Lif Measurements Of Multiple Ion Beamsmentioning
confidence: 99%
“…It was named current-free double layer (CFDL), as it formed self-consistently without external current forcing. The CFDLs formed in these experiments have later been repeated in a number of helicon devices [2][3][4][5][6][7][8][9]. As a result of a potential the drop set up between the source and the diffusion chamber an ion beam is formed.…”
Section: Introductionmentioning
confidence: 99%
“…In plasma applications, a directed ion flux is used to obtain an efficient momentum exhaust for electric propulsion, e.g., variable specific impulse magnetoplasma rocket, 4 and to achieve high aspect ratios in material processing ͑plasma etching͒. [5][6][7] Diverging magnetic field configurations are often used to obtain a unidirectional flow, [8][9][10][11][12][13] where we may anticipate that the magnetization of ions breaks down in the low magnetic field region. For realizing and controlling the plasma flow, it is important to have the knowledge on flow structure in the low magnetic field region, in which the detachment of ion stream line from the magnetic field line takes place.…”
Section: Introductionmentioning
confidence: 99%